â€œStudies on Prevalence and Multiple Antibiotic Resistance Patterns of E.coli Isolated from Drinking Waterâ€ - Hirulkar, N.B (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT E. coli is the primary cause of human urinary tract infections, as well as pneumonia, and traveler’s diarrhea. Waterborne diseases are among the leading causes of morbidity and mortality in developing countries and every year around 2.2 million people die due to basic hygiene related diseases like coliform diarrhoea. Antibiotic resistance is a type of drug resistance where a microorganism is able to survive exposure to an antibiotic. In the present study a total of 27 water sample collected randomly had poor hygiene area and a total of 18 E. coli isolates were identified. The overall spectrum of antibiotic resistance was showed that 2 isolates, Oxacillin and penicillin was highly resistance. 10 isolate resistance to Ampicillin, Cephalothin, Cephoxitin and Metronidazole. The spectrum showed variation in resistance. When study data analyzed for Over All Antibiotic Sensitivity it is found that out of total antibiotics more than 70% isolates showed sensitivity towards Piperacillin, Tetracycline, Vancomycim and Chloremphenicol and this drug can be recommended for elimination of E.coli. Thus these ï¬ndings recommended that Piperacillin and Vancomycim are the best choice of drugs, while the ofloxacin, cefdinir, ciproï¬‚oxacin and novobiocin antibiotics should be avoided against E coli diarrhoeal infections in this region.